Respostas

2014-01-17T12:30:02-02:00
Por Bhaskara temos:

Δ = b² -4ac
Δ = (-12)² -4 *9 * 4
Δ = 144 -144
Δ = 0
y' = (-b + √∆)/ 2a
(-(-12) + 0)/2 * 9
(12 + 0)/18
12/18
2/3

y'' = (-b - √∆)/ 2a
(-(-12) - 0)/2 * 9
(12 - 0)/18
12/18
2/3

S= {2/3,2/3}
4 4 4
2014-01-17T12:35:47-02:00
9y²-12y+4=0
a = 9 , b = - 12 , c = 4

Δ = b² -4ac
Δ = (- 12)² -4.9.4
Δ = 144 - 144
Δ = 0

x = -b ± √Δ
         2a

x = 12 ± 0
         18

x' = 12 + 0  
12  = 2 ou ≈ 0,6
          18       18     3

x" = 12 - 0   = 12 = 2  ou 
≈ 0,6
          18        18   3

S = {2 ; 2 }  
       3   3
9 4 9